APPLYING MIND MAPPING TECHNIQUE IN IMPROVING ENGLISH VOCABULARY MASTERY IN AN EFL CLASSROOM - Marzuki, Abdul Gafur (Paedagogia: Jurnal Pendidikan, 2017)
The aim of this study is to improve the EFL learners’ English vocabulary mastery through the application of mind mapping technique. The study employed the Classroom Action Research Design. The subject of this study was 49 undergraduate EFL learners at the Islamic Education Department FTIK IAIN Palu in 2016/2017 academic year. The data were collected through three research instruments: 1) vocabulary test, 2) observation sheet, and 3) field notes. This research was conducted in two cycles and each cycle was done in four meetings including the post cycle vocabulary test. The result of study shows that using Mind Mapping technique can improve the EFL learners’ vocabulary mastery. This is proved by the improvement of the EFL learners’ vocabulary test score results. In the first cycle, the average of the learners’ who fulfill the criteria of success is 55.1% which means that only 27 learners from 49 samples can pass the minimum standard score. In the second cycle, the result of the test is proved to increase into 85.7% which means that 42 of 49 learners have been successful to fulfill the criteria of success. Based on the result of the data analysis, it can be concluded that the EFL learners’ vocabulary mastery has been improved through the application of Mind Mapping Technique in the teaching of English.